Recent Trends of the Bio-Inspired Nanoparticles in Cancer Theranostics - Madamsetty, Vijay Sagar; Mukherjee, Anubhab; Mukherjee, Sudip (Frontiers in Pharmacology, 2019)
In recent years, various nanomaterials have emerged as an exciting tool in cancer theranostics applications due to their multifunctional property and intrinsic molecular property aiding effective diagnosis, imaging, and successful therapy. However, chemically synthesized nanoparticles have several issues related to the cost, toxicity and effectiveness. In this context, bio-inspired nanoparticles (NPs) held edges over conventionally synthesized nanoparticles due to their low cost, easy synthesis and low toxicity. In this present review article, a detailed overview of the cancer theranostics applications of various bio-inspired has been provided. This includes the recent examples of liposomes, lipid nanoparticles, protein nanoparticles, inorganic nanoparticles, and viral nanoparticles. Finally, challenges and the future scopes of these NPs in cancer therapy and diagnostics applications are highlighted.